EDUCATIONAL SERVICES DEVELOPMENT GUIDELINES FOR UNIVERSITY STUDENTS WITH DISABILITIES IN UPPER NORTH REGION - Jarunondrakul, Songklod; Tongsookdee, Ratchaneekorn; Vittayakorn, Soisuda; Leosiripong, Pikul (Journal of Buddhist Anthropology, 2022)
The objectives of this research article were to examine 1) State of educational services that Disability Support Services Center (DSS) provided at six universities in Upper North Region in accordance with the four strategies of education for individuals with disabilities in higher education 2) Satisfaction of student with disabilities (SWDs) with the services. And 3) Development guidelines for the services. Research methodology were mixed-methods. Study participants were six DSS staff and 120 SWDs who replied for research questionnaires, six DSS staff were chosen by Purposive sampling for interviews and 6 SWDs were chosen by Simple Random Sampling for focus groups. Research tools used included 1) questionnaires for DSS staff and SWDs, 2) interviews for DSS staff, and 3) focus groups for SWDs. Analyzed research data was reported using frequencies, percentages, mean, standard deviation and content analysis. The general findings showed that 1) the state of educational services in accordance of Strategy 1: Each of the universities had recruited SWDs using general exams and special projects; Strategy 2: The most services that SWDs had requested and received were tutoring services (66%); Strategy 3: Faculty members, staff, and students with or without disabilities participated in activities together in order to build a better understanding among each other through conversations; and Strategy 4: Collaborative projects with various agencies to promote employment opportunities were taken advantage by only a few of SWDs and, instead, they preferred to find desired jobs on their own. 2) Satisfaction level of SWDs with respect to the four strategies was all rated high. And 3) Development guidelines for DSS educational services: Practical accommodations that meet the needs of SWDs individually should be provided, and more effective channels of employment that meet specific needs of each individual graduate with disabilities should also be simultaneously promoted.